Analisis Pengaruh Time Management Terhadap Kedisiplinan dan Akademik Mahasiswa - Nika Sintesa (Universitas 45 Surabaya, 2023)
This study aims to analyze the role of time management and discipline academic in students. This research was conducted using a survey using student population as an object, samples were taken by sampling technique with a total of 30 students. The results of this study indicate that the effect of time management on students is influential. Thus, the conclusions that can be drawn from this study indicate that: students should be good at using and managing their time very well and effectively.